Dynamic model of the work team composition in the organization. (November 2020) - Kukartsev, V V; Tynchenko, V S; Dzhioeva, N N; Kukartsev, V A; Yamshchikov, A S
Abstract: The article presents a dynamic model of the composition of the labour collective in the organization. The model is built, taking into account the following categories of workers: «Executives», «Specialists», «Employees», «Workers» using Powersim Studio. Our model is multidimensional. A model management interface was created, which includes an input interface through which data is entered, as well as an output interface that allows seeing the difference between new employees and experienced ones. During the experiment, a model of the life cycle of an employee in an organization from hiring, adapting, working to experienced employees to the subsequent dismissal was considered. Based on the calculations, it was concluded that the recruitment rate, the speed of dismissals and the total number of employees affect the reception of new employees.